Board diversity and price informativeness for Malaysian top 100 public listed firms - Ooi, Ai Yee; Minah Japang; Suzillah Sidek (Universiti Malaysia Sabah, 2021)
This study examines the relationship between the diversity of board members and the price informativeness in the top 100 Malaysian public listed firms. By incorporating a series of the corporate governance and firm characteristic control variables, our findings indicate a negative relationship between ethnic diversity and price informativeness, suggesting that a less diverse board led to a more informative stock price. Nevertheless, gender diversity shows no significant impact. When the sample is divided into board with foreign director(s) and without foreign director, we find that the influence of ethnic diversity on price informativeness does not hold in the former firms. Our overall results imply that less ethnic diversity board reduces internal disagreement during board meetings. The existence of foreign directors mitigates the disagreement and thus undermine the influence of board ethnic diversity on price informativeness. Distinctively, our finding suggests that board foreign investors reduce the asymmetry information by importing corporate governance, yielding essential implications for policy makers.